2008
DOI: 10.1016/j.lfs.2008.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of multiple natural products in pancreatic cancer cells

Abstract: Pancreatic cancer (PC) remains the fourth most common cause of cancer related death in the United States. Therefore, novel strategies for the prevention and treatment are urgently needed. Numerous dietary and pharmacological agents have been proposed as alternative strategies for the prevention and/or treatment of PC. Isoflavone is a prominent flavonoid found in soy products and has been proposed to be responsible for lowering the incidence of PC in Asians. Similarly, curcumin, an active ingredient of turmeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…They also found that the effects of those compounds were associated with decreased Notch-1 expression and DNA binding activity of nuclear factor kappa B (NF-κB) and its target genes such as Cyclin D1, Bcl-2, and Bcl-xL [32]. …”
Section: Discussionmentioning
confidence: 99%
“…They also found that the effects of those compounds were associated with decreased Notch-1 expression and DNA binding activity of nuclear factor kappa B (NF-κB) and its target genes such as Cyclin D1, Bcl-2, and Bcl-xL [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Curcumin in combination with carnosic acid displayed a strong synergism in inhibiting acute myeloid leukemia cells accompanied by enhanced activation of apoptotic pathways (Pesakhov et al 2010). Combination treatment of curcumin plus isoflavone synergistically inhibited cell growth of BxPC-3 pancreatic cancer cells (Wang et al 2008). Furthermore, the combination treatment produced stronger inhibition on Notch 1 and NF-κB-mediated pathways than that attained by either compound alone.…”
Section: Other Cancersmentioning
confidence: 99%
“…Sufficient data from in vitro and in vivo experimental studies have produced solid evidence supporting the role of genistein as a potent anti-tumor agent by targeting multiple signaling pathways such as NF-κB, Wnt, Notch-1, and Akt/mTOR in many different types of cancers [193199]. Accumulating evidence from multiple in vitro and in vivo studies has also indicated that genistein exerts an anti-oxidant activity by inhibition of ROS production, DNA oxidation, lipid peroxidation, and NF-κB-mediated inflammatory cytokines in various cells including cancer cells [200207].…”
Section: Genistein a Soy Isoflavone As A Potent Anti-oxidant Agenmentioning
confidence: 99%